Soccer shoes reduce foot sensitivity compared to barefoot for external vibration stimuli - Sterzing, T.; Kunde, S.; Scholz, F.; Milani, T. L. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The human foot as a sensory organ uses tactile stimuli from its environment to adapt motor performance. Touch pressure and vibration stimuli are recognized by Merkel, Meissner, and Pacini skin mechanoreceptors. A sensitivity mapping for touch pressure and vibration stimuli showed different sensitivity levels of the numerous anatomical locations of the foot (Sterzing et al., 2006). Regarding motor performance, plantar foot sensitivity supports balance tasks (Perry et al., 2000). Foot sensitivity is likely to be decreased in athletes performing shod sports compared to athletes performing unshod sports (Schlee et al., 2007). This indicates the necessity to consider the role of footwear with respect to foot sensitivity in sports performance. For soccer players ball sensing is an important shoe property (Sterzing et al., 2007). Soccer shoes act as artificial interfaces between the foot and the ball. They need to protect the player`s foot but should also allow optimal ball handling, thereby supporting technical skills of the players. Sensory information is a crucial input variable for ball handling. Thus, the purpose of this study was to examine vibration sensitivity of the foot in different soccer shoe models compared to barefoot.